2015
DOI: 10.1159/000373960
|View full text |Cite
|
Sign up to set email alerts
|

CARD8 rs2043211 Polymorphism is Associated with Gout in a Chinese Male Population

Abstract: Background &Aim: Previous studies have suggested genetic factors are involved in the development of gout. We performed a case-control study to investigate the genetic association between CARD8 rs2043211 polymorphism and gout. Methods: A total of 396 male patients with gout and 403 age- and sex- matched healthy controls were included in this study. Genotyping was performed using TaqMan SNP Genotyping Assays. An association analysis was carried out using the χ2 test. The genotype-phenotype analysis was also cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
3
32
1
Order By: Relevance
“…This study identified that CARD8 rs2043211 was not associated with increased gout risk, which is in contrast to the known difference of genetic distribution of this SNP in the Chinese and European gout population (67). As far as we know, this study is the first to determine genetic association between the P2X7R SNP and gout patients, revealing that P2X7R polymorphism did not increase the risk of gout in our study population.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…This study identified that CARD8 rs2043211 was not associated with increased gout risk, which is in contrast to the known difference of genetic distribution of this SNP in the Chinese and European gout population (67). As far as we know, this study is the first to determine genetic association between the P2X7R SNP and gout patients, revealing that P2X7R polymorphism did not increase the risk of gout in our study population.…”
Section: Discussioncontrasting
confidence: 82%
“…McKinney et al (7) demonstrated that the prevalence of CARD8 rs2043211 was different between gout and control patients in the European and Polynesian populations (OR 1.11, P = 0.023 and OR 1.15, P = 0.078, respectively). Another case-control study showed that the MAF (A allele) CARD8 gene was shown to have an increasing trend relative to the T allele in the Chinese male population (OR = 0.084, P = 0.08) (6). However, our study revealed no association of CARD8 rs2043211 with the presence of gout in Korean study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SNP rs2043211 of CARD8 changes cysteine at codon10 to a premature termination codon, thus yielding a premature, truncated protein, which influences the protein function in inflammasome-mediated processes and NF-κB suppression [18,19]. Lots of studies show that the polymorphisms of CARD8 contribute to the development of some inflammatory diseases, such as inflammatory bowel disease [20][21][22], gout [23],abdominal aortic aneurysm [24], rheumatoid arthritis [17,25,26]and Alzheimer's disease [27,28]. As a part of innate immunity, CARD8 is involved in the modulation of inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%